The lock is the key - Maraković, Nikola (Acta chimica slovenica, 2017)
Modern drug discovery is mainly based on the de novo synthesis of a large number of compounds with a diversity of chemical functionalities. Though the introduction of combinatorial chemistry enabled the preparation of large libraries of compounds from so-called building blocks, the problem of successfully identifying leads remains. The introduction of a dynamic combinatorial chemistry method served as a step forward due to the involvement of biological macromolecular targets (receptors) in the synthesis of high affinity products. The major breakthrough was a synthetic method in which building blocks are irreversibly combined due to the presence of a receptor. Here we present various receptor-based combinatorial chemistry approaches. Huisgen's cycloaddition (1,3-dipolar cycloaddition of azides and alkynes) forms stabile 1,2,3-triazoles with very high receptor affinity that can reach femtomolar levels, as the case with acetylcholinesterase inhibitors shows. Huisgen's cycloaddition can be applied to various receptors including acetylcholinesterase, acetylcholine binding protein, carbonic anhydrase-II, serine/threonine-protein kinase and minor groove of DNA.
Keywords: dinamična kombinatorna kemija; drug design; dynamic combinatorial chemistry; Huisgenova cikloadicija; Huisgen's cycloaddition; načrtovanje zdravil